A feedback loop at the THERMOSENSITIVE PARTHENOCARPY 4 locus controls tomato fruit set under heat stress - Xiaonan Lu; Jianxin Wu; QianQian Shi; Shuai Sun; Yuan Cheng; Guozhi Zhou; Ren Li; Huanzhong Wang; Esther van der Knaap; Xia Cui (Nature Communications)
Abstract High temperatures compromise crop productivity worldwide, but breeding bottlenecks slow the delivery of climate-resilient crops. By investigating tomato fruit set under high temperatures, we discover a module comprising two linked genes, THERMOSENSITIVE PARTHENOCARPY 4a (TSP4a) and TSP4b, which encode the transcriptional regulators IAA9 and AINTEGUMENTA (ANT), respectively, to control thermosensitive parthenocarpy. TSP4a and TSP4b form a positive feedback loop upon heat stress to repress auxin signaling in ovaries. Natural TSP4a and TSP4b alleles bear regulatory-region polymorphisms and are differentially expressed to overcome the trade-off between fruit set and wider plant development. Gene editing of the TSP4a promoter and TSP4b 3’ UTR in open-chromatin regions results in expression down-regulation, increased parthenocarpy without yield penalties and maintenance of fruit-sugar levels without broad auxin-related pleiotropic defects in greenhouse-grown plants. These mechanistic insights into heat-induced parthenocarpy and auxin signaling in reproductive organs demonstrate breeding utility to safeguard tomato yield under warming scenarios.